2017
DOI: 10.5811/westjem.2017.7.34373
|View full text |Cite
|
Sign up to set email alerts
|

Effectiveness of SBIRT for Alcohol Use Disorders in the Emergency Department: A Systematic Review

Abstract: IntroductionAlcohol use disorders (AUD) place a significant burden on individuals and society. The emergency department (ED) offers a unique opportunity to address AUD with brief screening tools and early intervention. We undertook a systematic review of the effectiveness of ED brief interventions for patients identified through screening who are at risk for AUD, and the effectiveness of these interventions at reducing alcohol intake and preventing alcohol-related injuries.MethodsWe conducted systematic electr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

4
117
1
3

Year Published

2018
2018
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 123 publications
(125 citation statements)
references
References 72 publications
(130 reference statements)
4
117
1
3
Order By: Relevance
“…alcohol-related injury, reduced drinking and driving, increasing seat belt use, etc. ), while interventions focused on dependent drinkers or those meeting criteria for moderate or several alcohol use disorder focus on enhancing motivation to enter treatment [ 17 , 18 , 20 , 37 , 38 ]. Importantly, one observational study found that patients who received a direct referral, including transfer directly from the ED to a specialized treatment facility, were 30 times more likely to enroll in treatment than those with an indirect referral who are discharged home from the ED [ 38 ] (Table 1 ).…”
Section: Ed Interventions For Alcoholmentioning
confidence: 99%
See 1 more Smart Citation
“…alcohol-related injury, reduced drinking and driving, increasing seat belt use, etc. ), while interventions focused on dependent drinkers or those meeting criteria for moderate or several alcohol use disorder focus on enhancing motivation to enter treatment [ 17 , 18 , 20 , 37 , 38 ]. Importantly, one observational study found that patients who received a direct referral, including transfer directly from the ED to a specialized treatment facility, were 30 times more likely to enroll in treatment than those with an indirect referral who are discharged home from the ED [ 38 ] (Table 1 ).…”
Section: Ed Interventions For Alcoholmentioning
confidence: 99%
“…A 2008 study of harmful and hazardous drinkers did not detect a difference between patients receiving a BNI and scripted discharge instructions [ 42 ], although a second study of harmful and hazardous drinkers, that included universal screening and interactive voice response methodology to reduce assessment reactivity found reduction in mean past 7-day alcohol use and past 28 day binge episodes at 6 and 12 month follow-up in the BNI group and BNI group with 30 day booster over standard care [ 17 ]. A 2017 systematic review of ED studies using brief intervention or motivational interview based intervention to reduce alcohol consumption identified 25 randomized controlled trials; 13 studies showed decreased alcohol consumption at primary outcome; 17 studies failed to demonstrate intervention effect for primary outcome of alcohol consumption, 11 of which found significant results for either a specific subgroup or a secondary outcome [ 37 ]. Overall, authors conclude that there is moderate quality evidence for the targeted use of brief interventions that showed a small reduction in alcohol use in low or moderate drinkers and a reduction in the consequences of use such as injury [ 37 ].…”
Section: Ed Interventions For Alcoholmentioning
confidence: 99%
“…Such techniques typically involve helping the patient examine their relationship with alcohol and consider decreasing their levels of use to reduce the risk of further alcohol‐related harm. Barata and colleagues () reviewed 35 randomized controlled trials examining the impact of brief interventions for alcohol performed in the ED on subsequent alcohol use and related outcomes. They identified 13 studies that reported significant differences between control and intervention groups in the quantity and frequency of drinking after discharge that lasted from weeks to months.…”
Section: Discussionmentioning
confidence: 99%
“…There is limited evidence to support a small reduction in subsequent instances of alcohol-related injuries. 84,85 More research is needed to establish effective interventions for individuals presenting to the ED with complications of alcohol use.…”
Section: Behavioral Interventionsmentioning
confidence: 99%